Adverbial Accusative in the Arabic Language in the Work by Mustafa Ejubović Al-Fawa’idD Al-‘Abdtyya - Jahić, Mustafa (Prilozi za orijentalnu filologiju, 2017)
Mustafa Ejubović (1651- 1707) was among the best known Bosniak authors who wrote in Oriental languages. He wrote some thirty works of different size from a number of scientific fields. The majority of his works were from the fields of logic, disputes and several branches of Islamic law. He also wrote several works on Arabic grammar, stylistics and lexicography as well as on Islamic dogmatics and preaching. The subject of this paper is a grammatical analysis of the chapter on accusative in the Arabic language which, considering its syntactic-semantic function in the sentence, has the character of adverbials. Therefore, here we deal with the accusative of time and place, the accusative of purpose and aim, the accusative of state or manner and the accusative of specification. Entering into the syntactic relationship with its agent whose content they complement, these accusatives function, in the sentence, as definite time adverbials. As adverbial complements, they adverbially determine more closely the subject and the object of the sentence. They adverbially denote time or place, purpose or aim, state or manner and specification of certain content of the sentence expressed by its subject and object. The basis of Ejubović’ s work, whose chapter is dealt with in this paper, is az-Zamahshari’s work al-UnmUçhğ on the basis of which he explains the basic grammatical categories of Arabic grammar. Al-Fawa'id al-‘abdiyya, which is the titie of this work of Ejubović’s, therefore, is a complete work on the Arabic language grammar and, it can be claimed, at the same time the most important ١work of the sort in the Bosniak cultural heritage in the Arabic language. Ejubović explains these accusatives, frrst of ali, from the aspect of syntactic analysis, but with the support of other linguistic and sometimes non-linguistic Sciences, such as logic, for exarnple. With such an approach, which is compatible with the traditional interpretation of grammar, the author gives relatively complete interpretation of grammar issues and he displays the understanding of essence of eachparticular category. This is particularly relevant to the syntax of accusatives, since in other languages they are manifested differentiy, by means of a number of different grammatical means. At interpreting these grammatical categories the author, along with relying on the recognised authorities, which generally was the practice of the time in which he lived, often tried to explain some grammatical issues using his own explanations. In any case, in this chapter Ejubović manifested an extraordinary mastery of grammar as well as of a large number of sources and authors who he often quoted, which can be stated about the whole of his work. Nevertheless, bearing in mind that the work was designed for medresa students and as such cannot be expected to give more extensive and deeper explanation of grammar, al-Fawu ,id al-‘abdiyya, considering the quoted facts, still deserves an integral grammatical analysis and scientific evaluation.